Market as a factor in the development of mountain region in Montenegro - Jovanovic, Miomir; Despotović, Aleksandra (Economics of Agriculture, 2010)
Available surfaces, relief, climate, soil and hydro highlight specifc diversity of Montenegrin agriculture. Montenegro has a limited agricultural land (37.5% of the territory), arable land (36. 6% or 0. 3 ha per capita), and especially the area under arable land, orchards and vineyards (which are counted in the EU arable land), of only 58,262 ha or 0. 09 ha per capita. The hilly and mountainous region includes seven municipalities in northern Montenegro. Although this area is characterized by a signifcant share of nearly two ffths of total agricultural land and nearly so in total arable land in Montenegro (38.3%), one of the less developed region of Montenegro. The paper analyzes the current situation and perceived potential opportunities to improve this region from the market point of view.